The Influence of Service Quality and Product Price on Purchasing Decisions - Santoso, Teguh Iman; Lennysha, Lennysha (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – The researcher conducted this study to analyze the effect on service quality variables (X1) and product price variables (X2) on the variable purchase results (Y) at PT Lunindo in Batam City. This research uses quantitative methods and distributes data by distributing questionnaires. Methodology/approach – The population in this study were 149 people. Using data collection techniques with sampling techniques with non probability sampling techniques in Purposive sampling technique. The sampling method uses the Slovin formula at a significant level of 0.05 because respondents was 109 people, then the questionnaire will be distributed to 109 respondents. The next set, data collected through Assistance multiple regression of analysis and with program SPSS. Findings – The results of this study indicate the service quality variable (X1) and product price variable (X2) which have a positive and significant effect on the outcome variable purchase (Y) at PT Lunindo in Batam City. Service quality variable (X1) with positive and significant consideration of purchasing decisions (Y), and product price variables (X2) are fully understood positively and significantly towards purchasing decisions (Y). Simultaneously service quality (X1) and product price (X2) have a positive and significant effect on purchasing decisions (Y) at PT Lunindo in Batam City Novelty/value – Delve into the specific industry or sector that PT Lunindo operates within. Research could emphasize how service quality and product pricing impact purchasing decisions uniquely within that industry, potentially uncovering sector-specific patterns.